Rewrite, Repurpose, Reclaim: The Intertextual Reweaving of Australia’s Colonial History in Leah Purcell’s First Nations Adaptation Film, The Drover’s Wife: The Legend of Molly Johnson ... - Milnes, Delaney (The Australian National University, 2024)
This thesis closely reads Leah Purcell’s The Drover’s Wife: The Legend of Molly Johnson (2022) as both a film adaptation and a Fourth Cinema film. Analysing the understudied intersection between these fields shows how the adaptation process and Indigenous filmmaking techniques methodologically complement each other, especially in their retelling of stories and complicating of single-story approaches to history. I argue that the film interweaves these practices so as to respond to Australia’s colonial history, creating an alternate version of Henry Lawson’s “The Drover’s Wife” (1892) that rewrites First Nations peoples’ perspectives and experiences back into the archive. As a critical response to and creative rewriting of the archive, I read the film as engaging in postcolonial decolonising practices, notably the “critical-creative” practices of First Nations women writing against the archive. By linking the fields of adaptation and Fourth Cinema to explore their combined decolonising potential, rather than ...